Utilization of Technology in Early Childhood Education - Maria Fatima Mardina Angkur (Yayasan Adra Karima Hubbi, 2025)
Background. The use of technology in early childhood education is growing along with the advancement of digitalization. Technology can be an effective tool in improving children's learning experience, but its excessive use also poses challenges in their social and emotional development. Purpose. This study aims to analyze the impact of technology utilization on children's involvement in learning and identify the challenges faced in its implementation in the early childhood education environment. Method. This study uses a quantitative method with a descriptive approach. Data was collected through observations, interviews with educators, and questionnaires given to parents and teaching staff. Data analysis was carried out using descriptive statistical techniques and reliability validity tests. Results. The results of the study showed that technology had a positive impact on children's motivation and involvement in learning. Children who use interactive digital media show an improvement in material comprehension compared to conventional learning methods. However, several challenges such as limited access to technology and lack of educator skills in its use are still obstacles in the optimal application of technology. Conclusion. Technology has great potential in improving the effectiveness of early childhood learning when used with a balanced and directed approach. The use of technology needs to be supported by training for educators and policies that ensure equal access to technology for all children.